Should Japanese Universities Shift the Academic Calendar? - Shimmi, Yukiko (International Higher Education, 2013)
An effort to internationalize universities often conflicts with domestic systems, and it is seen at Japanese universities, currently. In Japan, to internationalize the university, a shift of the academic calendar from April to fall (September or October) was suggested by the internal panel of the University of Tokyo, in May 2012. This shift is to align the academic calendar to the world standard. Though this suggestion is still under discussion, major Japanese universities and the Japanese government, as well as industry, have started to discuss the issues and obstacles of implementation. While this suggestion might become a potential symbol of the reform for the internationalization of Japanese higher education, it has highlighted conflicts with traditional and domestic systems in many ways. Shifting the academic calendar faces difficulties at the University of Tokyo and other Japanese universities.